2022
DOI: 10.3389/fneur.2021.757050
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Reactivity to Hypercapnia Is Impaired in the Cerebral and Retinal Vasculature in the Acute Phase After Experimental Subarachnoid Hemorrhage

Abstract: Objective: Impaired cerebral blood flow (CBF) regulation, such as reduced reactivity to hypercapnia, contributes to the pathophysiology after aneurysmal subarachnoid hemorrhage (SAH), but temporal dynamics in the acute phase are unknown. Featuring comparable molecular regulation mechanisms, the retinal vessels participate in chronic and subacute stroke- and SAH-associated vessel alterations in patients and can be studied non-invasively. This study is aimed to characterize the temporal course of the cerebral an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The measurements of the vessel diameter of the retinal vessels did not give as homogeneous results as those of the cerebral vessels. The detailed analysis provided in our recent publication (see Figure 2 of the Supplementary material in Warner et al, 2022) showed stable reactivity over time with only selecting vessels with good reactivity at the beginning of the measurement phase. Considering all vessel segments at baseline, a higher variability is evident.…”
Section: Measurement Of Retinal Reactivity To Hypercapniamentioning
confidence: 94%
See 4 more Smart Citations
“…The measurements of the vessel diameter of the retinal vessels did not give as homogeneous results as those of the cerebral vessels. The detailed analysis provided in our recent publication (see Figure 2 of the Supplementary material in Warner et al, 2022) showed stable reactivity over time with only selecting vessels with good reactivity at the beginning of the measurement phase. Considering all vessel segments at baseline, a higher variability is evident.…”
Section: Measurement Of Retinal Reactivity To Hypercapniamentioning
confidence: 94%
“…In addition, two anesthetic protocols and the narcotics' effects on the cerebral and retinal vessels are described. The demonstrative examples used in this article are taken from the analysis performed in the context of our previous, already published study (Warner et al, 2022). Statistical analyses between and within anesthetic groups can be found in that study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations